Corrección de “Spanish Adaptation and Validation of the World Health Organization’s Violence Against Women Instrument” [Psicothema 35(2), 202-210] - Badenes-Sastre, Marta; Lorente Acosta, Miguel; Herrero Machancoses, Francisco; Expósito Jiménez, Francisca (Psicothema, 2024)
Sin resumen